Academic Stress and Associated Health Complaints Among Students During Online Education - .Shagufta Perveen; Haram Nazir; Sehrish Khan (PJDOL, 2022)
The current study was carried out to explore the role of academic stress with health complaints among students experiencing online education and find out the demographic difference in these variables. In the present study along with the demographic sheet three instruments, Academic Stress Scale (Bedewy & Gabriel, 2015), and the Chinese Health Questioner (Fong, Yip, & Ho, 2021), were administered to a sample of 200 students experiencing online education. Results of the study revealed that academic stress has a significant negative association with the health complaints of the student. The results also showed that gender has significant differences in academic stress and health complaints whereas age has a non-significant negative relationship with academic stress and a significant positive relationship with health complaints. The result also demonstrated significant academic discipline and mode of instruction-based differences in academic stress and health complaints among students.